2021
DOI: 10.3389/fcvm.2021.681948
|View full text |Cite
|
Sign up to set email alerts
|

The Notch Pathway: A Link Between COVID-19 Pathophysiology and Its Cardiovascular Complications

Abstract: COVID-19 is associated with a large number of cardiovascular sequelae, including dysrhythmias, myocardial injury, myocarditis and thrombosis. The Notch pathway is one likely culprit leading to these complications due to its direct role in viral entry, inflammation and coagulation processes, all shown to be key parts of COVID-19 pathogenesis. This review highlights links between the pathophysiology of SARS-CoV2 and the Notch signaling pathway that serve as primary drivers of the cardiovascular complications see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 167 publications
1
27
0
1
Order By: Relevance
“…Notch signaling has also been known to facilitate viral infectivity of RNA viruses including influenza virus, respiratory syncytial virus (RSV), HCV, etc. ( Breikaa and Lilly, 2021 ) and have regulatory roles in inflammation ( Shang et al, 2016 ). Our study is concordant with an earlier study that reported the downregulation of the Notch signaling in CCHFV-infection at the transcript level ( Arslan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling has also been known to facilitate viral infectivity of RNA viruses including influenza virus, respiratory syncytial virus (RSV), HCV, etc. ( Breikaa and Lilly, 2021 ) and have regulatory roles in inflammation ( Shang et al, 2016 ). Our study is concordant with an earlier study that reported the downregulation of the Notch signaling in CCHFV-infection at the transcript level ( Arslan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has also been implicated in contributing to the development of cytokine storm in COVID-19 patients, a signaling pathway for which we could also identify several putative viral inducers ( Table 1 ) [ 23 ]. Similarly, the role of the Notch pathway in promoting the pro-inflammatory microenvironment and cardiovascular diseases (e.g., myocarditis, thrombosis) that are associated with COVID-19 is well-established, but it is still unknown which SARS-CoV-2 factors are involved in the dysregulation of the Notch pathway [ 24 , 25 ]. We identified at least five viral inducers that could play a role in the regulation of the Notch signaling pathway in SARS-CoV-2-infected cells ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of a high autoantibody response to these proteins suggests that they are overproduced during a pathological condition, such as cancer or a cardiovascular complication 39, 40 . For example, notch signally protein RBPJ has been associated with COVID-19 pathophysiology and cardiovascular complication 41 . Similarly, keratin family proteins (KRT19 and KRT15) that are responsible for epithelial cell structural integrity are linked to COVID-19 pathogenesis and disease severity 42 .…”
Section: Discussionmentioning
confidence: 99%